The role of inflammation in childhood asthma. (1st June 2000) - Chedevergne, Frederique; Le Bourgeois, Muriel; de Blic, Jacques; Scheinmann, Pierre
Abstract : The role of inflammation in adult asthma is well known, involving a cascade of immunological stimulation in which mast cells and eosinophils play pivotal roles. However, the assessment of airway inflammation in children is more difficult as the invasive methods used in adults cannot ethically be used for this purpose alone. Nevertheless, limited data from studies using invasive methodology, and studies using novel non-invasive techniques such as sputum induction and nitrous oxide exhalation, are improving knowledge. The immunopathology in childhood asthma appears to mirror that in adult sufferers. The inflammatory processes are evident at an early age in wheezing infants who later develop asthma, and there are different "wheezing phenotypes" in children with atopic asthma or viral associated wheeze. The mechanisms underlying childhood asthma are dependent not only on increased numbers of inflammatory cells in the airways, but also increased activation of these cells. In vitro data have shown that corticosteroids can inhibit the secretion of proinflammatory compounds from alveolar macrophages, suggesting a potential important role for these agents in halting the development of asthma. Techniques for measuring inflammation in infants need to be refined, in order to provide increased knowledge and accurate monitoring of the disease. It is hoped that this will enable the development of early interventions to minimise the impact of asthma in infants who are identified as being susceptible.